Bilateral advancement flaps in the treatment of divided nevus of the eyelid - Yan Yu; Fan Dai; Jie Gao; Tao Liu; Haijuan Sun; Yanrong Li (Medicine, 2026)
Divided eyelid nevus can affect facial appearance and is difficult to reconstruct after excision. We conducted a retrospective case series (N = 11) and reported the study according to the STROBE guidelines. Eleven patients aged 1–10 years with congenital divided eyelid nevi underwent single-stage excision followed by bilateral advancement flaps and canthal anchoring. Outcomes were evaluated using the Vancouver Scar Scale (VSS) and parent/guardian satisfaction scores. The median VSS score was 1 (interquartile range, 1.5). The mean parent/guardian satisfaction score was 2.45/3, and more than half of patients rated the outcome as “excellent.” Healing was generally uncomplicated, and no severe complications occurred. Minor flap necrosis and asymmetry of the palpebral fissure were noted in a few patients, but these improved within 6 months. Overall, the flaps survived well, and eyelid contour was maintained. This modified single-stage approach provided good cosmetic and functional results and may be a safe and effective option for congenital divided eyelid nevi.